Abnormal Resting-State Functional Connectivity of Insular Subregions and Disrupted Correlation with Working Memory in Adults with Attention Deficit/Hyperactivity Disorder - Zhao, Qihua; Li, Hui; Yu, Xiaoyan; Huang, Fang; Wang, Yanfei; Liu, Lu; Cao, Qingjiu; Qian, Qiujin; Zang, Yufeng; Sun, Li; Wang, Yufeng (Frontiers in Psychiatry, 2017)
Objectives: Executive function deficits are major impairments in adults with attention deficit/hyperactivity disorder (ADHD). Previous studies have shown that the insula is involved in cognitive and executive functions. However, the insula is highly heterogeneous in function, and few studies have focused on functional networks which related to specific insular subregions in adults with ADHD. We explored the functional networks of the insular subregions (anterior insula [AI], mid insula [MI], and posterior insula [PI]). Furthermore, their correlations with self-ratings of ecological executive functions, including inhibition, shifting, and working memory were investigated. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) data in 28 adults with ADHD and 30 matched healthy controls (HCs) were analyzed. The seed-based resting-state functional connectivity (RSFC) of the insular subregions were evaluated. We also investigated their associations with the Behavior Rating Inventory of Executive Function-Adult Version (BRIEF-A) inhibition, working memory, and shifting factor scores. Results: Compared with HCs, adults with ADHD showed altered RSFC of the AI, with the precuneus, precentral gyrus, and inferior temporal gyrus extended to the middle temporal gyrus, lingual gyrus and superior occipital gyrus, respectively. There were no significant differences in RSFC of the MI and PI between the two groups. Within the HC group, working memory scores were associated with the RSFC of AI with precuneus and temporal gyrus. However, there was no correlation between these variables in the ADHD group. Conclusion: The study evaluated RSFC patterns of the insular subregions in adults with ADHD for the first time. Altered RSFC of the anterior insula which is a crucial region of salience network (SN) and part of regions in default mode network (DMN), were detected in adults with ADHD in both results with and without global signal regression (GSR), suggesting that disrupted SN-DMN functional connectivity may be involved in EF impairments in adults with ADHD, especially with respect to working memory. Deficits of the anterior insula which is involved in salient stimuli allocation, might be associated with the pathophysiology of ADHD. The inconsistent results of MI and PI between analyses with and without GSR need further exploration.